2020
DOI: 10.3389/fpsyg.2020.01972
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Experience and Omnichannel Behavior in Various Sales Atmospheres

Abstract: The conceptual framework for our analysis is the approach to environmental psychology first introduced by different authors in 1974. Subsequently in 1982 this concept was applied to retail outlets so as to better understand the effect on consumers of atmospheric stimuli experienced in a physical store. Following the developing trend from traditional marketing to new online sales channels, various authors have sought to transfer and validate these theories with virtual outlets or e-stores, so as to validate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…In addition, retailers can appropriately adjust layouts or designing interfaces to enhance shopping atmospheres and customer experiences. Paz and Delgado ( 2020 ) indicate that digital atmospheres are important to prompt online sales. Under the season with heavy smog pollution, retailers can change the design and layout of online platforms to help customers reduce anxiety and anxiety.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In addition, retailers can appropriately adjust layouts or designing interfaces to enhance shopping atmospheres and customer experiences. Paz and Delgado ( 2020 ) indicate that digital atmospheres are important to prompt online sales. Under the season with heavy smog pollution, retailers can change the design and layout of online platforms to help customers reduce anxiety and anxiety.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This study adopts the S-O-R framework as its overarching theory. As a widely used theory in the consumer behavior literature (Zheng et al, 2019 ; Akram et al, 2020 ; Arif et al, 2020 ; Paz and Delgado, 2020 ; Lim et al, 2021 ; Wang et al, 2022 ), this model emphasizes how environmental stimuli lead to cognitive and affective responses (i.e., perception, experience, and evaluation), which in turn trigger certain psychological responses (i.e., attitudinal and behavioral responses) (Mehrabian and Russell, 1974 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Some studies have shown that the higher the level of uncertainty, the stronger the perceived risk ( Chen and Chang, 2012 ; Liang et al, 2018 ). In addition, uncontrollable factors increase with the virtuality of the network environment, and these uncertainties all increase the perceived risks ( Shao et al, 2019 ; Paz and Delgado, 2020 ). This study focus on the customer’s expectation perception of loss in the process of using the e-commerce platform, including the subjective psychological perception of various possible consequences after consumption.…”
Section: Literature Reviewmentioning
confidence: 99%